Thermomechanical behavior of tunnel linings in the geothermal environment: Field tests and analytical study. (July 2023) - Wang, Qiling; Wang, Mingnian; Yuan, Yong; Hu, Yunpeng; Wang, Hui
Abstract: Geothermal environment brings challenge to the construction and maintenance of tunnels. This motivates the present study on the thermomechanical behavior of the supporting system of these tunnels. Evolution of the temperature and strain fields of the surrounding rock and linings of three representative cross-sections were monitored in field. These sections exhibit significant difference in the initial geothermal temperature, reading as 28 . 2 ∘ C, 45 . 4 ∘ C, and 68 . 6 ∘ C, respectively. The measurements indicate that, with an increase of the initial geothermal temperature, the speed of the temperature drop of the surrounding rock increases after the excavation, whereas the thermal shock resulting from the construction of secondary lining becomes less obvious. Significant tensile strains were observed in the primary lining, as a result of the geothermal environment. This stimulates the establishment of a simplified arch model in quantification of the thermal stresses of the primary lining. The quantitative thermoelastic analysis indicates that the high geothermal environment leads to remarkable tensile stresses at the vault of the outer surface and at the side wall of the inner surface, which counteracts with the released heat from the cast in-situ concrete of the secondary lining. It is concluded that geothermal environment raises the risk of tensile cracking of tunnel linings. Therefore, careful inspection is recommended for its integrity and, thus, for the long-term durability of such tunnel linings. Highlights: Temperature and strain evolution of high geothermal tunnel were monitored in field. An arch model was established to quantify thermal stresses of primary lining. High geotherm leads to large temperature drops and thermal strains after excavation. Primary linings of tunnels, in a geothermal temperature of 68.6 °C, may crack.